2011
DOI: 10.1007/s12603-011-0067-8
|View full text |Cite
|
Sign up to set email alerts
|

Validity of retrospective diet history: Assessing recall of midlife diet using food frequency questionnaire in later life

Abstract: Objectives Limited information exists on the validity of dietary information given by elderly people on their past diet. Here we test the relative validity of a food frequency questionnaire asking older persons about their midlife diet. Design Retrospective food intake of 56–72-year-old subjects was estimated using a food frequency questionnaire designed for the AGES-Reykjavik Study (AGES-FFQ), an epidemiological study of older individuals. Results were compared with detailed dietary data gathered from the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
56
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 33 publications
(59 citation statements)
references
References 15 publications
(21 reference statements)
0
56
1
2
Order By: Relevance
“…Foods and food groups were selected for the questionnaire on the basis of their contribution to the absolute intake of elderly Icelanders according to a National Nutrition Survey [24] as well as their unique nutritional qualities and possible connection to the development of various diseases in later life. The questionnaire has been described previously [20, 21]. …”
Section: Methods/subjectsmentioning
confidence: 99%
See 3 more Smart Citations
“…Foods and food groups were selected for the questionnaire on the basis of their contribution to the absolute intake of elderly Icelanders according to a National Nutrition Survey [24] as well as their unique nutritional qualities and possible connection to the development of various diseases in later life. The questionnaire has been described previously [20, 21]. …”
Section: Methods/subjectsmentioning
confidence: 99%
“…Validity of questions on midlife diet and current diet has been assessed in previous studies, and milk was among the foods that showed the highest validity [20, 21]. Midlife milk intake of 56–72-year-old individuals was estimated retrospectively using the questions on midlife diet in the AGES-FFQ and results compared with detailed dietary data, gathered from the same individuals 18–19 years previously, i.e., in midlife, as a part of a national dietary survey [24].…”
Section: Methods/subjectsmentioning
confidence: 99%
See 2 more Smart Citations
“…The FFQ for midlife was validated with dietary data gathered from the same individuals in midlife (Reykjavik Study), and late-life intake was validated against weighed dietary intake. Correlations for fish liver oil ranged from 0.42 to 0.56 (P , 0.001) (20,21). Early-life dietary habits have not yet been validated but are consistent with residency dependent dietary habits (i.e., higher fish consumption in coastal areas) (22).…”
Section: Fish-oil Consumptionmentioning
confidence: 99%